KEPEMIMPINAN KONTEMPORER DALAM PENDIDIKAN ISLAM - Afriandi; Rihlah Fauziah Wahab; Safira Lulu Salvana; Rikawati; Ririn Afrianti; Nurul Mufidah; Alfian Siddiq Jafar (TEKNOS: Jurnal Pendidikan dan Teknologi, 2024)
This research reviews contemporary leadership concepts in Islamic education through literature reviewmethods. Highlighting the characteristics, challenges and opportunities faced by Islamic education leaders, this research also identifies the principles and best practices that support the achievement of quality and relevant Islamic education goals. Integrating the results of the latest literature review, this journal aims to provide in-depth insight into the role and leadership in improving the quality and relevance of Islamic education in an ever-changing global context. In addition, this article highlights challenges such as the lack of adaptation to changing times, the prevalence of corruption, dishonesty, and the lack of morality and competence of leaders in Islamic education in the millennial era. Proposedsolutions include community-based leadership education, character education, and conflict managementthrough emotional intelligence. It is hoped that by applying these principles, Islamic education leaders can face the challenges of the millennial era and bring positive changes to the society and institutions they lead.